The karyotype of the crossbred between the Murrah and Malaysian swamp buffalo (bubalus buballs) - Bongso, T. A. (Persatuan Doktor Veterinar Malaysia, 1979)

(untitled)
Chromosome analysis on cultured peripheral blood leucocytes demonstrated that the Fl cross of Murrah X Malaysian swamp buffalo (Bubalus bubalis) had a diploid chromosome number of 49 and a karyotype intermediate to that of the parents. The effect this chromosome complement may have on fertility is discussed.